Pelayanan Petugas Pasasi Dalam Menangani Special Passanger (Wheelchair) PT. Gapura Angkasa Bandar Udara Internasional I Gusti Ngurah Rai Bali - Prisma Maydita Nugrahani; Anita Nur Marsyi’ah (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to find out many cases of passengers who have special conditions due to illness, disability, the elderly, pregnant women, disabilities, the visually impaired and their children cannot do it alone, for that they need special services, namely in the form of wheelchair users to help their journey while at the airport. This study uses qualitative research methods. The data collection techniques used are observation, interviews, documents and documentation as well as observations. The researcher immediately made observations, the researcher also explained the results of the data taken during the interview and observations for the interview, the researcher interviewed 3 resource persons with document data obtained by the researcher from the documentation of the activities of the medical officer in handling the Special Passanger (Wheelchair) when carrying out duties and responsibilities in the field and also in the form of implementation documents for the data analysis techniques used, namely Data collection, data reduction, presentation of discussion data and conclusions. The results of this study include, the performance of the Pasasi unit in Handling Special Passengger (Wheelchair) at PT. The Angkasa Gate of I Gusti Ngurah Rai International Airport Bali has been very good in terms of work quality, work quantity, responsibility, cooperation, and initiatives which all aspects have been very well carried out by the Pasasi unit officers in handling special passengers. Officers must have experienced obstacles, obstacles here such as the wheelchair that is used is not suitable for use such as the wheelchair wheel sounds, Wheelchair passengers do not have a companion in carrying out flights, and wheelchair passengers do not bring a statement letter and other obstacles often occur experienced by the transit officer.